Microstructure Evolution Of Isothermally Aged Ecaped Sac Solder Alloy - Zulkifli, Nur Amiera (Universiti Sains Malaysia, 2017)
In recent years, Sn-Ag-Cu solder alloy has been found to be amongst the suitable candidate for replacement of the conventional tin-lead (Sn-Pb) solder. Despite the advantages of SAC solder, the current demand of interconnect material prefers a higher mechanical properties of solder which would provide higher reliability of solder joint. In this project, a severe plastic deformation approach, namely an Equal Channel Angular Pressing (ECAP) technique used on SAC 305 solder in order to increase mechanical properties. The focus is on the influence of ECAP grain refinement to the IMC behaviour during isothermal aging. Characterization of the solder alloys focused on microstructure of bulk solder, IMC layer at solder joint during reflow and IMC growth during isothermal aging. The reflow process was done at 270°C whereas aging was performed isothermally at 180°C for 100 hours, 250 hours and 500 hours. Microstructure of bulk solder and the interfacial IMC formed were observed using FE-SEM equipped with EDX. Hardness of the bulk solder was measured via micro Vickers hardness tester whereas tensile strength of solder joint was evaluated using a lap joint shear test. ECAP processing with route A resulted in elongated and thin β-Sn dendrites while route Bc produced fine equiaxed β-Sn dendrites. The hardness of solder increased with number of ECAP passes while the IMC layer of solder joint decreased with higher number of passes. Isothermally aged samples with route A showed thicker IMC layer when the aging time is longer. ECAP with 9 passes possessed the lowest tensile strength due to the presence of many pores in solder joint.